Perancangan Cetakan Batu Bata Dengan Metode Pahl And Beitz - Pasaribu, Rismauli Novianty; Silviana, Nukhe Andri; Siregar, Ninny; ., Susilawati (Fakultas Teknik UMSU, 2025)
Along with the development of technological products that can provide comfort and convenience for human life which will depend on the innovation of more complex product functions for consumers that will continue to be used, therefore it is necessary to design lightweight brick molds that are ergonomic and able to meet customer demands. The design of the lightweight brick mold was carried out using the Pahl and Beitz method by applying the REBA (Rapid Entire Body Assessment) method for proposed improvements by evaluating the worker's overall posture. The aim of this research is to produce an ergonomic design that is able to meet every customer request. The results of the research showed that measurements of work posture carried out by light brick workers had to take corrective action because it showed level 10, which means it was at level 4 (dangerous conditions). By reducing dangerous angles on body parts, a better working body posture is obtained with a REBA score of 3 which is included in risk level 2 (Low risk) based on worker anthropometric processing where each data is sufficient and uniform, so that a lightweight brick mold design can be produced. reduces the risk of injury to musculoskeletal disorders for workers with dimensions of mold length 100 cm, width 51.27 cm, mold height 60 cm, mold handle length 29 cm, mold handle width 9 cm